THE EFFECT OF INTRINSIC MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE ENGAGEMENT MEDIATED PERFORMANCE AT PT XYZ - Arifin, Ridwan; Johanes Lo, Singmin (Dinasti Publisher, 2020)
This study aims to analyze the influence of intrinsic motivation and organizational culture on employee performance mediated by employee engagement. The object of this research is the employees of PT XYZ. A total of 100 respondents filled out a questionnaire, the sample was taken using a saturated sample of 100 employees. This research was conducted from October 2019 to April 2020 at the PT XYZ office. The sampling technique used was saturated sampling. Data were analyzed using the Smart PLS (Partial Least Square) path analysis application. The results of this study indicate that Intrinsic Motivation and Organizational Culture have a positive and significant effect on performance. Meanwhile Employee Engagement becomes a mediation between Intrinsic Motivation and Organizational Culture on Performance. Employee Engagement perfectly mediates Intrinsic Motivation. And Employee Engagement partially mediates Organizational Culture.